Deciding what to research: an overview of a participatory workshop. (20th February 2014) - Northway, Ruth; Hurley, Karen; O'Connor, Chris; Thomas, Helen; Howarth, Joyce; Langley, Emma; Bale, Sue
<x xml:space="preserve">Abstract</x> Accessible summary People with learning disabilities are involved in doing research more and more. A lot of papers have been written about this. These papers sometimes do not say whether people with learning disabilities decided what should be researched. This paper talks about how a group of people with learning disabilities and professionals worked together to decide what research they should do in their area. Summary While recent years have seen an increase in the number of participatory and inclusive research studies being undertaken where people with learning disabilities are active members of the research team, little has been published about how teams decide what to research. This paper aims to fill this gap by discussing how in one area of Wales a participatory workshop was held to try and identify priority areas for research. By sharing our experiences, we hope that other people will be encouraged to try similar approaches. First, however, this activity is set in the context of wider debates concerning participatory research.